Mouthwashes Available Nationally in Drugstore Chains, with a focus on complementary componentes - Araújo, Roberto Paulo Correia de; Mendes, Carlos Maurício Cardeal; Araújo, Danilo Barral de; Dantas, Sarah Souza Lima Nery (Revista de Ciências Médicas e Biológicas, 2026)
Introduction: Mouthwashes are widely used as a complement to daily oral hygiene. Their formulations, which are constantly evolving, vary significantly among commercially available products. Among the main antiseptic agents used are cetylpyridinium chloride, chlorhexidine digluconate, triclosan combined with Gantrez polymer, and essential oils. In addition, mouthwashes include a variety of substances generically referred to as ““other components””, as described in their respective leaflets. Objective: This study aimed to identify and analyse mouthwashes available on the national market, with an emphasis on the “other components” listed in their formulations. The research focused on products sold in drugstores in the city of Salvador, Bahia. Methodology: Data collection was conducted in person in three Administrative Regions (ARs) of Salvador, Bahia, covering stores of the Drogasil, São Paulo, and Pague Menos chains. Technical information regarding the active ingredients, concentrations, formulations, and “other components” present in mouthwashes containing antiseptics was collected. The information obtained from drugstores was supplemented with data available on the manufacturers' websites to ensure completeness and reliability, with particular attention to the variability of “other components”, regardless of the main active ingredient. The analysis considered product labelling and its validation through official online sources. Results: The analysis of the labels of mouthwashes sold in three drugstore chains, located in different Administrative Regions (ARs) of the city of Salvador, Bahia, identified a total of 16 different products. Regarding the “other components” present in the formulations, it was found that all products contained water and flavouring. The presence of sodium saccharin was observed, on average, in 91.3% of the products evaluated in the three regions. Colourants were present in 88.0% of the mouthwashes analysed, and sorbitol in 88.8%. It was also observed that active ingredients with antiseptic action tend to be repeated among products, often associated with a relatively uniform additional composition, regardless of brand or retailer. This pattern suggests partial standardisation in the formulation of mouthwashes available in the local market. Conclusion: The data highlight the need for greater rigour and transparency in the information provided on mouthwash labels and leaflets, particularly concerning the precise identification of active ingredients, a detailed description of other formulation components, and the recommended dosage for safe and effective use. This transparency is essential to warn of possible adverse effects, such as oral irritation, mouth ulcers, or hypersensitivity reactions, particularly in more sensitive individuals. Additionally, special attention is recommended for children's formulations containing fluoride ion, which should present uniform concentrations and avoid combination with antiseptics to ensure greater safety for paediatric patients.